Philosophy as a system - Kubalica, Tomasz (Folia Philosophica, 2011)
Review of Christian Krijnen's book “Philosophy as a System: Principle-Theoretical Investigations into the Concept of System in Hegel, Neo-Kantianism, and Contemporary Philosophy.” Würzburg: Königshausen & Neumann, 2008.